Antibiotic Resistance and the Biology of History. (December 2016) - Landecker, Hannah
Beginning in the 1940s, mass production of antibiotics involved the industrial-scale growth of microorganisms to harvest their metabolic products. Unfortunately, the use of antibiotics selects for resistance at answering scale. The turn to the study of antibiotic resistance in microbiology and medicine is examined, focusing on the realization that individual therapies targeted at single pathogens in individual bodies are environmental events affecting bacterial evolution far beyond bodies. In turning to biological manifestations of antibiotic use, sciences fathom material outcomes of their own previous concepts. Archival work with stored soil and clinical samples produces a record described here as 'the biology of history': the physical registration of human history in bacterial life. This account thus foregrounds the importance of understanding both the materiality of history and the historicity of matter in theories and concepts of life today.